2012
DOI: 10.1007/s11158-012-9186-2
|View full text |Cite
|
Sign up to set email alerts
|

Africa Humiliated? Misrecognition in Development Aid

Abstract: Critiques of development aid from its recipient's sometimes draw our attention to the perception of paternalism on the part of 'development industry' actors. Even within participatory project designs, critical voices recount experiences of clear power divides and informal hierarchies determining the content and form of 'cooperation'. While neoliberal as well as neo-Marxist scholars base their critiques on a distributive scheme of global justice, post-development theory emphasizes respect and recognition as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Finally, the lack of verifiable numbers leads to a reliance on ''experiential' access to the past' (Charbakaty 2007, p. 79). Lived experience may be contested as a source of knowledge, in itself a form of misrecognition, an 'epistemic injustice' which limits those who are misrecognised in having their knowledge claims heard (Dübgen 2012). Though non-Māori and/or non-adopted historians narrated histories that included Māori adoptees, it was the lived experience of being-Māori-and-adopted that led to this re-interrogation of the historical record.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the lack of verifiable numbers leads to a reliance on ''experiential' access to the past' (Charbakaty 2007, p. 79). Lived experience may be contested as a source of knowledge, in itself a form of misrecognition, an 'epistemic injustice' which limits those who are misrecognised in having their knowledge claims heard (Dübgen 2012). Though non-Māori and/or non-adopted historians narrated histories that included Māori adoptees, it was the lived experience of being-Māori-and-adopted that led to this re-interrogation of the historical record.…”
Section: Discussionmentioning
confidence: 99%
“…Another concern for humanitarian intervention is that it may become an exacerbating influence. This concern has received considerable attention in the literature surrounding development aid and humanitarian interventions (see Moyo 2001;Lentz et al 2005;Assal 2008;Dübgen 2012;Cunningham 2012, among others). Some researchers, like Lentz et al (2005), found no causal link between the provision of food aid and dependency.…”
Section: Escaping the Cycle Of Dependencymentioning
confidence: 99%
“…A common explanation for this type of ignorance is the lack of inclusion of people who have epistemic authority and first-hand knowledge on the subject matter. This is an issue that is commonly brought up by scholars from feminist and decolonization studies (Dübgen 2012). In some cases, these mistakes are a product of well-meant intentions; the firm commitment to treat everyone as equals may hinder people to recognize vulnerabilities and privileges even in cases where they ought to.…”
Section: Closing Epistemic Gaps: Designing and Implementing Poverty-smentioning
confidence: 99%